Fast fabrication of THz devices by femtosecond laser direct writing with a galvanometer scanner. (11th April 2019) - Dai, Zijie; Su, Qiang; Wang, Yunfei; Qi, Pengfei; Wang, Xiaolei; Liu, Weiwei
Abstract: Terahertz (THz) functional devices are essential to THz applications. In this paper, we proposed a feasible method for the fast fabrication of THz devices based on a femtosecond laser direct writing system with a galvanometer scanner. A wire-grid THz polarizer and a cross-shaped band pass THz filter were fabricated in this way and the overall processing time was greatly shortened to within 15 min. Then a THz time domain spectroscopy system was applied to verify the experimental performance of these THz devices, which was in good agreement with the simulation results. This fabrication method can be further scalable to other THz devices, which is promising to facilitate THz applications.